Pengaruh (Matrik) Pola Susunan Serat Terhadap Karakterisktik Peredam Suara Berbahan Sabut Kelapa - Asrul Ainun Najah; Ikhwanul Qiram; Dewi Sartika (Virtual of Mechanical Engineering Article, 2020)
Noise is something that can be annoying. A silencer is a tool to reduce unwanted sound. This study aims to obtain the matrix characteristics of the fiber arrangement pattern on sound attenuation and the ratio of the composite material mixture. The method used in this research is to vary the ratio of flinkote oil mixtures 70%: 30%, 60%: 40%, 50%: 50%, as well as variations in the matrix pattern of coconut fiber composition with parallel matrices, straight oblique cross, how to make composites with how to spray flinkote oil onto the fibers using a spray gun. The analysis of the research is the reduction of the sound produced. The ratio of the mixture and the matrix of the fiber arrangement pattern affects the resulting sound reduction value. The results showed that the flinkote oil mixture ratio of 60%: 40% resulted in the highest reduction value of 4.96%, for the lowest results found in the ratio of flinkote oil mixture 50%: 50% fiber with a noise reduction value of 4.24%. The results of the analysis show that the ideal mixture occurs in composites of 60%: 40%, so that the flinkote oil can bind the fibers sufficiently and the composites are porous, in the 50%: 50% composites there are strains because the flinkote oil is unable to bind the fibers. In the fiber arrangement pattern matrix, there is the highest noise reduction value in the parallel matrix, namely 4.96%, for the lowest result is in the straight-sloping matrix with a reduced value of 3.90%, the analysis results in the parallel matrix have good noise wave propagation, because In the parallel matrix there is no wave interference phenomenon, resulting in parallel propagation of noise waves, in the straight-sloping matrix there is an interaction phenomenon between incoming waves and waves called interference so that noise waves increase and result in a low noise reduction level.